Soft-constraint based satisfactory fault-tolerant control for discrete-time systems - Dengfeng Zhang; Yu Han; Chao Zhao; Wei Zhang (2015 International Conference on Control, Automation and Information Sciences (ICCAIS), 2015)
The active fault-tolerant control (FTC) with multiple performance constraints is investigated for a class of discrete-time systems subject to sensor faults. A satisfactory FTC strategy by way of the online moving horizon control mode is proposed to guarantee the closed-loop stability of the faulty system. The corresponding soft-constraint based FTC controller design method is developed from the predictive control theory to handle the multiobjective requirements including the constraints on relative stability, control input and system output, and the optimized quadratic performance as well. Its main advantage is to avoid the infeasibility of the online FTC controller reconfiguration due to the inconsistent constraints by relaxing soft constraints. The optimization calculation in the design can be executed by various nonlinear programming algorithms to solve the intrinsic nonlinear and non-convex constraints, which is an obstacle for conventional linear- and convex-based algorithms. Finally, an example is presented to verify the effectiveness of the proposed satisfactory FTC method.